Ruthenium tetroxide oxidation of N-methyl-isoxazolidine: Computational mechanistic study - Maria Assunta Chiacchio; Daniela Iannazzo; Salvatore V. Giofrè; Roberto Romeo; Laura Legnani (Arabian Journal of Chemistry, 2022)
In this paper, we report a mechanistic study of RuO4-catalyzed oxidation on the 2-methylisoxazolidine through computational methods. The investigation was performed taken into consideration that the oxidation could take place on different sites of the substrate. This reaction occurs in two steps, involving a double H-transfer. In particular, the rate-determining one implies a [3 + 2] one-step, but asynchronous mechanism. In the first step, when methyl propanoate is used as solvent, the formation of an ion pair, which affords to the product, is involved. Furthermore, the study highlights that all carbon atoms of the isoxazolidine system, near to the heteroatoms, can undergo the oxidation process. The detected selectivity is correlated to the stability of the corresponding carbocations, leading to the N-methylisoxazolidin-3-one as preferred product.